Social Attitude Analysis of 4th Grade of SDN 2 Kebumen in Industrial Revolution 4.0 - Suhartono, Suhartono; Karimizzah, Diyani Ayu; Sandhi, Dwi Pungky Ari (Universitas Sebelas Maret, 2019)
The industrial 4.0 was the impact of the disruptive and development of the human mind pattern. In this era people will live with the help of technology so sophisticated that it affects social attitudes. The study served to describe the impact of the industrial revolution on students' social attitudes and to describe the students' social attitudes on learning. This research is a qualitative descriptive study, data collection techniques use interviews, questionnaire, and observation. The subject of this study is a 4th grade at SDN 2 Kebumen as many as 18 student, parent and 4th grade teachers. The results of this study shows that industrial era 4.0 cause students' poor social attitude when there is no supervision and direction from teachers and parents. On learning indicates that 4th grade students have varying degrees of social attitudes that cause learning to be less conducive.